Microcephaly: tracing the evolutionary lineage of ASPM gene. - Mushtaq Hussain; Muhammad Asif Qureshi; Rafiq Muhammad Khanani; Abdul Wajid; Shaheen Shoaib Sharafat; Talat Mirza (Journal of the Dow University of Health Sciences, 2010)
Objective: Microcephaly, in the form of congenital autosomal recessive disorder (MCPH), is characterized by the reduced occipital frontal head circumference >3 standard deviation of otherwise normal population of matching age and sex. The disease is primarily associated with mild to severe mental retardation. Earlier studies have unravelled that among Pakistan population, mutations in ASPM gene is strongly associated in MCPH.